Service receipt of adults with rare genetic syndromes who engage in challenging behaviour. Issue 3 (3rd July 2018) - Awan, N.; Oliver, C.; Wilde, L.; Eden, K.; Waite, J.
ABSTRACT: Background: There is limited research documenting the health and/or psychological services accessed by adults with rare genetic syndromes who engage in challenging behaviour. The study documented service receipt and associations with person characteristics. Method: Thirty-two parents of adults with rare genetic syndromes completed an adapted version of the Client Service Receipt Inventory. Access to services for general health and challenging behaviour in the last six months were documented. Person characteristics measured were: adaptive behaviour, autism spectrum disorder characteristics, impulsivity and overactivity. Results: Over half of adults who engaged in challenging behaviour did not receive professional input for behaviours. No association was found between the degree of challenging behaviour and service receipt for challenging behaviour. Total activity score (impulsivity and overactivity) was positively associated, and adaptive ability negatively associated, with accessing professionals. Conclusions: Service receipt is not appropriately linked to needs. Further research should examine factors that affect service access including individual characteristics and service experience.